Combination of robot-assisted glove and mirror therapy improves upper limb motor function in subacute stroke patients: a randomized controlled pilot study - Jin Qian; Chong Liang; Run Liu; Jingyi Yu; Tangzhu Yang; Tangzhu Yang; Dingqun Bai (Frontiers in Neurology)
ObjectiveThis pilot study aimed to investigate the effects of combining mirror therapy with robot-assisted glove therapy (RMT) on upper limb functional recovery in patients with post-stroke hemiplegia.MethodsFifty-two patients with subacute stroke were randomly assigned to three groups mirror therapy (MT) group, robot-assisted therapy (RT) group or RMT group-using a computer-generated randomization table. Patients in all three groups received routine rehabilitation training, MT group received mirror therapy on the basis of this, RT group received rehabilitation robot glove training on the basis of conventional rehabilitation treatment, and the RMT group received rehabilitation robot glove training and mirror therapy at the same time. All interventions lasted for 4 weeks, 5 times a week. Before treatment, 4 weeks after treatment, Fugl-Meyer Assessment-Upper Extremity (FMA-UE), Brunnstrom Hemiplegic Rating Scale, Functional test for the Hemiplegic Upper Extremity–HongKong (FTHUE-HK), Functional Independence Measure (FIM) were used to evaluate the upper limb function and activities of daily living (ADL) of patients.ResultsCompared with baseline, FMA-UE, Brunnstrom upper limb and hand grade and FIM score were observed across all three groups post-intervention (p < 0.05). Compared with MT group, FMA-UE (37.61 ± 11.09), Brunnstrom upper limb (4.06 ± 0.87) and hand grades (4.67 ± 1.24) and FIM scores (94.17 ± 9.49) in RMT group were superior after treatment (p < 0.05), and the differences were statistically significant.ConclusionMirror therapy combined with rehabilitation robot glove may be an effective treatment method to improve the upper limb function, promote the recovery of motor function and improve the ability of daily living of patients with hemiplegia in subacute stroke.